Osteoimmunology of tumor necrosis factor-alpha, IL-6, and RANTES/CCL5: a review of known and poorly understood inflammatory patterns in osteonecrosis - Lechner J; Rudi T; von Baehr V (Dove Medical Press, 2018)
Johann Lechner,1 Tatjana Rudi,2 Volker von Baehr3 1Clinic for Integrative Dentistry, Munich 81547, Germany; 2Institute for Epidemiological Studies, Berlin 10709, Germany; 3Department of Immunology and Allergology, Institute for Medical Diagnostics in MVZ GbR, Berlin 12247, Germany Background: The immune and bone systems are closely linked via cytokine cross-talk. This interdisciplinary field of research is referred to as osteoimmunology and pertains to inflammatory and osteoarticular diseases that feature the primary expression of tumor necrosis factor-alpha (TNF-α) and IL-6.Objective: Are there bone resorptive processes wherein chronic inflammatory conditions are not linked to TNF-α and IL-6 expression, but rather to the expression of other cytokines?Materials and methods: A comprehensive literature search was performed in PubMed Central.Discussion: Although all diseases with cytokines involved in bone resorption (TNF-α and IL-6) are at the forefront of destructive inflammatory processes, there is one exception in the literature: fatty oxide osteoporosis/osteolysis in the jawbone (FDOJ), which is associated with significant bone softening. However, it should be noted that TNF-α and IL-6 fall below the levels found in a healthy jawbone in this condition. Another conspicuous finding is that there is a nearly 35-fold overexpression of the chemokine RANTES/CCL5 (R/C) in all FDOJ cases studied thus far in the literature. Conclusion: FDOJ appears to represent a unique cytokine and inflammatory pattern from osteolysis in the body. R/C can be defined as the dominant carrier of a “maxillomandibular osteoimmunology”. Keywords: bone resorption, chemokine RANTES, CCL5, tumor necrosis factor-alpha, maxillomandibular osteoimmunology, maxillomandibular